Forest-friendly pedagogy (PeRIMBA) at indigenous school : risk and risk perceptions - Mohd. Najib Haron; Rozilah Kasim; Nur Bahiyah Abdul Wahab; Sharifah Nurulhuda Tuan Mohd Yasin; Siti Aminah Kusin (RedWhite Press, 2020)
The Forest-friendly pedagogy (PeRIMBA) refers to the implementation of outdoor learning session by using forest elements as the learning aid and site. There are four basic principles of PeRIMBA which known as supportive environment, task divided into small portions, the usage of natural surroundings and the involvement of all the senses. The implementation of PeRIMBA introduces a risk-taking approach that will offer the opportunities for teachers and students to engage in risky activities during learning session. This risky activity may seem daunting but if the risks are well managed, the learning sessions will be meaningful. In promoting meaningful learning especially to the indigenous school, Malaysia Ministry of Education support and highlight two intervention action plan that promote flexible classroom and fun learning. Flexible curriculum delivery is not dependent on classroom learning only and fun learning promotes the integration and application of forest elements. However, this intervention action plan needs further research and study especially in the field of risk. The emergence of a social science perspective in the field of risk research has opened up new perspectives to define, measure, and explain the concept of risk. Some of the new risk components proposed in social science studies such as shock, threat, danger, lack of control, and uncertainty. Moreover, the fear and unknown factors are components that influence the perceptions of risk. The input on risk and risk perception will be an added value to teachers to implement PeRIMBA in their teaching and learning sessions. These concepts then lead to risk perception that, in turn, influenced risk assessment and risk management.